Asymptomatic Bacterial Vaginosis in Pregnancy and Missed Opportunities for Treatment: A Cross-Sectional Observational Study - Nkosinathi Joyisa; Dhayendre Moodley; Thandeka Nkosi; Raesetja Talakgale; Motshedisi Sebitloane; Megeshnee Naidoo; Quarraisha Abdool Karim (Hindawi Limited, 2019)
Background. High rates of bacterial vaginosis (BV) have been described in nonpregnant South African women. Studies of BV in South African pregnant women are sparse. Diagnosis and prompt treatment of BV in pregnancy are expected to have a positive impact on pregnancy outcomes and HIV prevention. This study was undertaken to determine the prevalence of BV in pregnant women in a high HIV burden periurban setting in KwaZulu-Natal and explore how to enhance BV diagnosis in this setting where syndromic management of sexually transmitted diseases is the standard of care. Methods. In this cross-sectional study, consenting HIV uninfected pregnant women were examined for abnormal vaginal discharge; nurses determined the vaginal pH and collected a vaginal swab for Gram-stain and Nugent scoring. Findings. Among 750 HIV uninfected pregnant women, 280 (37.3%; 95%CI 33.9-40.9) tested positive for BV. Using a vaginal pH > 4.4, 65% of women with BV were correctly identified, while an abnormal vaginal discharge correctly identified a significantly lower proportion (52.9%) of women with BV (p=0.005). The sensitivity, specificity, and positive and negative predictive values of vaginal pH testing were 65.9% (95%CI 60.0 - 71.5%), 61.4% (95%CI 56.8 - 65.9%), and 50.1% and 75.4%, respectively. The 20-24 year-old pregnant women were twice more likely to test positive for BV than the adolescent pregnant women (43.6% vs 21.1%) (p = 0.037) and BV was not associated with the duration of a sexual relationship, frequency of unprotected sex during pregnancy, number of lifetime sex partners, or the partner's age. Conclusion. There is a high burden of primarily asymptomatic BV in HIV uninfected pregnant women in this periurban setting. Both the sensitivity and specificity of vaginal pH testing are superior to the symptomatic diagnosis of BV but not good enough to be used as a screening tool.